Critical discourse analysis of Fajriatun Nurhidayati’s Nyadran-Belajar Toleransi pada Tradisi - Chamalah, Evi; Nuryyati, Reni; Azizah, Aida (EduLite: Journal of English Education, Literature and Culture, 2023)
Critical Discourse Analysis is a form of analysis that aims to reveal ideology, power, political attitudes, and gender. In this study, Critical Discourse Analysis is used to reveal the ideology and power contained in the language used by the author in Nyadran's book. Every discourse that discusses a topic of ideology and power always contains prejudice. This is what makes language expressions contain symbolic meanings. The critical discourse analysis that has been carried out in Nyadran-Belajar Toleransi pada Tradisi by Fajriyatun Nurhidayati can be concluded that to express ideology in a literary text, language cannot be placed in a closed manner. Nonetheless, the context within a literary text serves as a crucial factor in shaping discourse ideology. Furthermore, literary works are inherently intertwined with the author's creative circumstances, thereby rendering the interpretation of textual meaning inseparable from the employed language. Within this examination, it's evident that ideology in literary compositions and language itself defies rigid categorization, underscoring the significance of the contextual backdrop as a fundamental influencer on the ideology woven into the discourse.